Hubungan Upah Industri dan Pengeluaran Per Kapita Terhadap Inflasi di Kalimantan dengan Pendekatan Metode Regresi - Linda Linda; Nor Anisa (Majalah Ilmiah METHODA, 2025)
This study aims to analyze the influence of average industrial sector wages and per capita expenditure on inflation in Kalimantan using the multiple linear regression method. The data used includes annual average industrial sector wages and per capita expenditure as independent variables, with the inflation rate as the dependent variable. The analysis results indicate that average industrial sector wages have a significant impact on inflation, while per capita expenditure contributes on a smaller scale. The applied inflation prediction model demonstrates a fairly good level of accuracy with an RMSE value of 0.010 ± 0.000. However, significant deviations between predicted and actual values were observed at certain points, such as inflation rates of 0.015 and 0.04, highlighting limitations in the model. The findings imply that an increase in industrial sector wages could drive inflation due to higher production costs passed on to consumers. Conversely, higher per capita expenditure shows a weaker correlation with inflation but still contributes to increased consumption. This study is expected to serve as a reference for policymakers in formulating more effective strategies to control inflation in Kalimantan, such as managing industrial sector wages and enhancing household purchasing power.